2022
DOI: 10.1007/s00737-021-01202-8
|View full text |Cite|
|
Sign up to set email alerts
|

Diversity in high-impact psychiatric publishing: gender parity within reach?

Abstract: Gender parity and authorship diversity are declared goals in the publishing world. This study assessed the progress of authorship gender distribution over a quarter of a century and geographic diversity over the last 15 years in high-impact psychiatric journals. All articles published in 2019 in the American Journal of Psychiatry, the British Journal of Psychiatry, and JAMA Psychiatry were included and compared with data from three points in time starting in 1994. Descriptive statistics were gathered, and chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A total of 473 articles were published in 2019. Of those 234 (49.5%) were original research articles, of which 118 were published by females as first authors ( 15 ). In 2014, the total number of published articles was 642.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 473 articles were published in 2019. Of those 234 (49.5%) were original research articles, of which 118 were published by females as first authors ( 15 ). In 2014, the total number of published articles was 642.…”
Section: Resultsmentioning
confidence: 99%
“…Limited to three high-impact journals, the results of this study cannot be generalised to medium- or low-impact journals. Additionally, it should be taken into account that the majority of papers were published by authors from high-income areas, mainly North America and Europe ( 15 ). An analysis of social psychiatric research from Germany showed similar results with regard to mental health conditions under study, with articles on psychiatric patients in general ranked first, followed by schizophrenia, substance-related disorders and affective disorders ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations